2011
DOI: 10.1099/vir.0.029678-0
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic identification of a novel anellovirus in Pacific harbor seal (Phoca vitulina richardsii) lung samples and its detection in samples from multiple years

Abstract: To investigate viral pathogens potentially involved in a mortality event of 21 Pacific harbor seals (Phoca vitulina richardsii) in California in 2000, viral metagenomics was performed directly on lung samples from five individuals. Metagenomics revealed a novel seal anellovirus (SealAV), which clusters phylogenetically with anelloviruses from California sea lions and domestic cats. Using specific PCR, SealAV was identified in lung tissue from two of five animals involved in the 2000 mortality event, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 41 publications
2
60
0
1
Order By: Relevance
“…RNA viral sequences were not observed in our data, and since the sequence coding the replication protein from this putative virus contained premature stop codons, similar sequences would have been excluded from our analyses. Sequences similar to those from the Anelloviridae, which occur in insects and mammals including California sea lions and Pacific harbor seals (Ng et al, 2011), were not found in our samples, suggesting that they were rare or too divergent to be assigned to the family. Viruses from the Parvoviridae family have linear genomes and would not be enriched by MDA, and were excluded from this analysis.…”
Section: Resultsmentioning
confidence: 80%
“…RNA viral sequences were not observed in our data, and since the sequence coding the replication protein from this putative virus contained premature stop codons, similar sequences would have been excluded from our analyses. Sequences similar to those from the Anelloviridae, which occur in insects and mammals including California sea lions and Pacific harbor seals (Ng et al, 2011), were not found in our samples, suggesting that they were rare or too divergent to be assigned to the family. Viruses from the Parvoviridae family have linear genomes and would not be enriched by MDA, and were excluded from this analysis.…”
Section: Resultsmentioning
confidence: 80%
“…Viral nucleic acids were first nonspecifically amplified using random hexamers by rolling-circle amplification (Genomiphi; GE Healthcare) and then further amplified by specific primers designed to amplify the whole circular genome using inverse PCR (70,71). PCR amplicons were then Sanger sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…2c). The amino acid sequences were aligned using Mafft 5.8 [2] with the E–INS–I alignment strategy and previously described parameters [5, 6]. A maximum-likelihood tree was created using RaxML based on the Mafft alignment with previously described parameters [6, 10].…”
mentioning
confidence: 99%